Using citizen science data to uncover the invasion of the non-native fish, Hemibagrus wyckioides (Fang and Chaux, 1949) in Peninsular Malaysia - Aqmal-Naser, Mohamad; A. Ghani, Intan-Faraha; Abdullah Halim, Muhammad Rasul; Fahmi-Ahmad, Muhammad; Khaironizam, Md. Zain; Azmai, Mohammad Noor Amal; Zakaria, Zahar Azuar; Ilham-Norhakim, Mohd Lokman; Ahmad, Amirrudin B. (Springer Nature, 2024)
Knowledge on the distribution of non-native fishes is critical to assess the current status of biological invasions and prevent further spread and impacts. This study aims to synthesize current distributional data of the non-native catfish, Hemibagrus wyckioides, an emerging invader in Peninsular Malaysia. We collected occurrence data from Facebook groups created by anglers and freshwater fish enthusiasts, which were used to map the distribution of the species. A total of 106 occurrences of H. wyckioides were recorded in five states, with three major invasion hotspots identified—Selangor, Pahang and Perak. Given the scarcity of distributional data for this species within the published literature, social media platforms provided invaluable information on the current distribution of this emerging invader, highlighting their potential utility in early detection and monitoring of poorly-known non-native fishes.